2022
DOI: 10.1371/journal.pone.0276464
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time fast PCR amplification using designated and conventional real time thermal cycler systems: COVID-19 perspective

Abstract: The study aimed to shorten multiplex RT-PCR run time for detection of SARS CoV-2 N1 and N2 sequences and human RNase P (RP) sequence as internal mRNA control using conventional and designated real time thermal cycler systems. Optimization of Fast PCR protocol using plasmid-based N1 and N2 positive control and synthetic version of human RP was done on Applied Biosystems (ABI) QuantStudioTM5 (conventional), ABI 7500 Fast Dx (designated), and CFX96 Touch Real Time Detection System, Bio-Rad (conventional). Finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This lower linearity could be attributed to the “ultra-rapid” thermal cycling utilized by PicoGene ( 18 20 ). Even the “fast mode” of the conventional real-time PCR instrument showed a tendency toward lower linearity under fast PCR conditions ( 27 , 28 ). However, despite the lower linearity, the limit of detection achieved by PicoGene with the CDC N1/N2 duplex assay was 1 copy/µL ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This lower linearity could be attributed to the “ultra-rapid” thermal cycling utilized by PicoGene ( 18 20 ). Even the “fast mode” of the conventional real-time PCR instrument showed a tendency toward lower linearity under fast PCR conditions ( 27 , 28 ). However, despite the lower linearity, the limit of detection achieved by PicoGene with the CDC N1/N2 duplex assay was 1 copy/µL ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…But some of the mutations acquired during the evolution of the viral genome may lead to failure in RT-PCR amplification, for instance the 69-70 del in the S gene [ 9 , 10 ] as well as mutations occurring in the N gene [ 11 , 12 ]. Globally, this technique is considered the gold standard for the diagnosis of COVID-19 due to its sensitivity; therefore, many industries had developed commercial kits to reduce the typical run time and improve the methodology protocol [ 13 , 14 , 15 ]. The importance of a solid and proven stability of genomic regions is pivotal to design targets for a diagnostic kit, therefore in this study we compared 48 samples identified during the daily diagnostic workflow presenting a PCR peculiar result.…”
Section: Introductionmentioning
confidence: 99%
“…However, the time required is longer than that for other tests, owing to the time required for nucleic acid extraction and amplification [ 17 ]. Therefore, studies have aimed to shorten the assay time by focusing on pooled testing, nucleic acid extraction, and PCR amplification [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%